A pseudo-planar metasurface for a polarization rotator - Chia, Elbert E. M. (2014)
New demonstrations of effective interaction between light and artificially electromagnetic interface, or the metasurface, have stimulated intensive research interests on control of light to realize applications in beam steering, optical imaging and light focusing, etc. Here we reported a new type of planar metasurface of which every individual metamolecule is single metallic layer with stereo structure and the metasurface is name as Pseudo-Planar Metasurface (PPM). The metamolecule of the PPM is a chiral structure and therefore derives significant optical activity.